(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
This research entitled (Area of handling and operation and the possibility of functional performance in the port of Zuwara _ a field study) aims to identify the relationship between the total area of the port and the efficiency in job performance and the total climatic and soil factors that affect the reduction of the area prepared for operation and the possibility of various types of equipment and equipment as well as the port facilities Represented in the open yards, covered stores, sidewalks, and breakwaters, in addition to identifying the differences between the factors affecting performance by identifying the operational areas by measuring the dimensions of the port facilities in a way that shows the evaluation of the performance rate and its relationship to the cadastral maps. Although man is currently living in an era that is pervaded by distinctive technical characteristics and scientific innovations, it is not without human exposure to exciting and difficult situations under the current circumstances. Through the results of the field study, it became clear that the commercial port of Zuwara needs to be re-evaluated for all the standards of commercial ports according to the required quality standards in order to be able to carry out the functional tasks for the safety of ships and port operators.